THE GEOPOLITICAL AWAKENING OF THE EUROPEAN UNION AGAINST THE BACKDROP OF THE RUSSIAN-UKRAINIAN WAR - Buriachenko, Oleksii (Scientific Journal of Polonia University, 2024)
The article analyses the impact of the Russian-Ukrainian war on the geopolitical transformation of the European Union (EU). It examines the key changes in the EU’s security, energy and international relations strategy, as well as the development of its strategic autonomy and role in supporting Ukraine. The study is based on the analysis of scientific sources and political articles related to the EU’s foreign policy and security mechanisms. A comparative analysis of the EU’s decisions on sanctions, energy security and military assistance to Ukraine is used. Expert assessments of the geopolitical situation and economic consequences of the war are also taken into account. The article contributes to understanding the role of the Russian-Ukrainian war as a catalyst for the EU’s political and strategic awakening. In particular, it highlights the development of the EU’s strategic autonomy in response to its energy dependence on Russia and the growth of defence cooperation between member states. The author also explores how the war has contributed to the consolidation of European identity and the strengthening of the desire for global leadership in the face of current international challenges. The author notes that the Russian-Ukrainian war has accelerated changes in the EU’s approach to foreign and security policy. The EU has strengthened its strategic autonomy, increased economic sanctions against Russia and mobilised resources to support Ukraine. At the same time, the war has shown the need to develop energy resources independent of external suppliers and to increase the EU’s internal defence capabilities. Ukraine’s integration into the European space has become an important strategic direction of the EU’s policy. An important aspect has been the strengthening of European defence cooperation, which demonstrates the EU’s desire for greater independence in security matters. Ukraine’s integration into the European space is becoming one of the key directions of the EU’s foreign policy, which may accelerate the process of Ukraine’s accession to the Union in the future. The author also draws attention to the fact that the issue of strengthening the EU’s defence capabilities affects the problem of the international security system, which today, as a result of the Russian-Ukrainian war, is undergoing the greatest transformations since the Second World War.